2011
DOI: 10.4104/pcrj.2011.00082
|View full text |Cite
|
Sign up to set email alerts
|

Measuring walking speed in COPD: test-retest reliability of the 30-metre walk test and comparison with the 6-minute walk test

Abstract: Aims: To examine test-retest reliability of the 30-metre walk test (30mWT) in patients with chronic obstructive pulmonary disease (COPD) and to compare the 30mWT with the 6-minute walk test (6MWT).Methods: Forty-nine subjects with stable COPD were included. The 30mWT consists of walking at different walking intensities over a distance of 30 metres -self-selected speed (ss-30mWT) and maximal speed (ms-30mWT). The test was conducted twice and the time to walk 30 metres was recorded. The 6MWT was performed in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
4
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 48 publications
4
29
4
1
Order By: Relevance
“…This indicates that, for this population, the test is reproducible with reproducibility values similar to those obtained using other clinical exercise tests, such as 6-min walk test, which presents an ICC of 0.88 -0.94, [20][21][22] and shuttle-walk test, which presents an ICC of 0.87. 23 Moreover, the error value for this comparison was acceptable, presenting a mean error of 5.7 steps and limits of agreement ranging from Ϫ7.1 to 18.6 steps.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…This indicates that, for this population, the test is reproducible with reproducibility values similar to those obtained using other clinical exercise tests, such as 6-min walk test, which presents an ICC of 0.88 -0.94, [20][21][22] and shuttle-walk test, which presents an ICC of 0.87. 23 Moreover, the error value for this comparison was acceptable, presenting a mean error of 5.7 steps and limits of agreement ranging from Ϫ7.1 to 18.6 steps.…”
Section: Discussionsupporting
confidence: 75%
“…Standard error of measurement as a percentage of the mean was 5%, which was similar to the same error analysis using the 6-min walk test in other studies that also represented ϳ5% of the mean performance of the test. 21,25 These results show that the performance in this test was not influenced by the learning effect in the COPD population, which leads to the affirmation that this test can be done without a familiarization test, spending only 15 min of assessment time. This characteristic could be an advantage over the 6-min walk test, which requires at least one previous test and a recovery time between them, totaling a time expenditure of at least 50 min.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Our group had better test-retest reliability for the usual 10-meter gait speed (ICC of 0.97 vs 0.87) when comparing with the usual 30-meter gait speed measured in a smaller COPD cohort. 14 This study showed that in patients with COPD, there is good agreement between stopwatch and automated timing system measurements for usual gait speed measurements. That agreement did not hold true with maximal walking speeds.…”
Section: Discussionmentioning
confidence: 62%
“…12,13 However, those studies did not evaluate the several commonly described gait speed protocols and have not established the effect of distance walked, pace, or timing methods on the reliability and reproducibility of gait speed results in patients with COPD. Prior studies using fast pace 14,15 have not investigated the commonly used distances (4 and 10 meters) or the possible timing systems. Variability in the methodology is believed to affect clinical interpretation and implementation of the gait speed measures.…”
Section: Introductionmentioning
confidence: 99%